Norwegian modals - Eide, Kristin M., 1965- (Studies in generative grammar, 2005)
Norwegian Modals is a detailed description of the syntactic and semantic properties of modals in Norwegian. The book thoroughly and critically evaluates previous proposals from the modality literature, focusing on argument structure, scopal properties and the interplay of modals with tense and aspect. After presenting a range of new data and generalizations, a new analysis is proposed, incorporating recent developments in generative linguistic theory and the construction of a new compositional tense system. This investigation is highly relevant for the study of modals and modality in Germanic and other languages. It will also be of value to linguists working on argument structure, tense and aspect, and to those interested in Scandinavian languages.